Functional Polymorphisms in Oxytocin and Dopamine Pathway Genes and the Development of Dispositional Compassion Over Time: The Young Finns Study - Dobewall, Henrik; Saarinen, Aino; Lyytikäinen, Leo-Pekka; Keltikangas-Järvinen, Liisa; Lehtimäki, Terho; Hintsanen, Mirka (Frontiers in Psychology, 2021)
Background. We define compassion as an enduring disposition that centers upon empathetic concern for another person’s suffering and the motivation to act to alleviate it. The contribution of specific candidate genes to the development of dispositional compassion for others is currently unknown. We examine candidate genes in the oxytocin and dopamine signaling pathways. Methods. In a 32-year follow-up of the Young Finns Study (N = 2130, 44.0% men), we examined with multiple indicators latent growth curve modeling the molecular genetic underpinnings of dispositional compassion for others across the life span. We selected five single nucleotide polymorphisms (SNPs) whose functions are known in humans: rs2268498 (OXTR), rs3796863 (CD38) (related to lower oxytocin levels), rs1800497 (ANKK1/DRD2), rs4680 (COMT), and rs1611115 (DBH) (related to higher dopamine levels). Compassion was measured with Cloninger’s Temperament and Character Inventory on three repeated observations spanning 15 years (1997–2012). Differences between gender were tested. Results. We did not find an effect of the five SNPs in oxytocin and dopamine pathway genes on the initial levels of dispositional compassion for others. Individuals who carry one or two copies of the T-allele of DBH rs1611115, however, tend to increase faster in compassion over time than those homozygotes for the C-allele, b = 0.063 (SE = 0.027; p = .018). This effect was largely driven by male participants, 0.206 (SE= 0.046; p<.001), and not significant in female participants when analyzed separately. Conclusions. Men who are known to have, on average, lower compassion than women seem to reduce this difference over time if they carry the T-allele of DBH rs1611115. The direction of the association indicates that dopamine signaling activity rather than overall dopamine levels might drive the development of compassion.